2010
DOI: 10.1007/s10495-010-0489-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human PDCD5 sensitizes chondrosarcomas to cisplatin chemotherapy in vitro and in vivo

Abstract: Clinical management of chondrosarcoma remains a challenging problem, largely due to the toxicity and resistance of this tumor to conventional chemotherapy. Programmed Cell Death 5 (PDCD5) is a protein that accelerates apoptosis in different cell types in response to various stimuli, and has been shown to be down-regulated in many cancer tissues. In this study, mRNA and protein levels of PDCD5 were found to be up-regulated in cisplatin-treated SW1353 chondrosarcoma cells compared with untreated cells. Recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…This conclusion is consistent with previous reports in chondrosarcoma 21 and colorectal cancer. 22 Taken together, previous research and our data indicate that PDCD5 promotes chemosensitivity of malignant tumors by activating mitochondrial pathway. Therefore, combination of PDCD5 with chemotherapeutic agents is expected to be a very effective strategy for the treatment of tumors.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This conclusion is consistent with previous reports in chondrosarcoma 21 and colorectal cancer. 22 Taken together, previous research and our data indicate that PDCD5 promotes chemosensitivity of malignant tumors by activating mitochondrial pathway. Therefore, combination of PDCD5 with chemotherapeutic agents is expected to be a very effective strategy for the treatment of tumors.…”
Section: Discussionsupporting
confidence: 83%
“…The results are in accordance with previous reports which showed that PDCD5 sensitizes chondrosarcomas or colorectal cancer to cisplatin chemotherapy. 21,22 In addition, we found that PDCD5 also increased chemosensitivity to CBDCA and VCR. However, PDCD5 had no significance effect on sensitivity of glioma cells to VP16.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A combination of both in vitro and in vivo experiments confirmed that tumor cells expressing PDCD5 or treated with recombinant PDCD5 protein were more sensitive to chemotherapeutic drugs and UV irradiation. For example, mice with tumors expressing PDCD5 and treated with chemotherapy or radiation showed increased apoptosis, decreased tumor growth, and prolonged survival (8)(9)(10)(11)(12). These results support a role for PDCD5 as a tumor suppressor that influences treatment and prognosis.…”
Section: Introductionmentioning
confidence: 73%
“…Instead, it seems to be a pro-apoptotic factor that cooperates with chemotherapy or UV irradiation to cause cell death (8)(9)(10)(11)(12). In several studies, increased PDCD5 expression is accompanied by its translocation from the cytoplasm to the nucleus, a process that occurs prior to cell death.…”
Section: Introductionmentioning
confidence: 99%